Evaluation of the " out-reach programmes " and some related aspects of the school dental service in Ratnapura District - Konthasinghe, P.P (My University, 1996)
This study was undertaken in 1995/96 to assess the impact of out-reach programmes and other related aspects of school dental service on the prevention and treatment of dental caries and periodontal disease among school children of Ratnapura District. The study also assessed the current oral health status in school children in the Ratnapura administrative district. Further, the study makes as attempt to compare and contrast this data with those of the national oral health survey of 1983/84.The results confirmed a greatly enhanced coverage of the target population. There is an encouraging trend towards achieving the objective of the minimum 50 per cent coverage of the target population by year 2000.It also indicated an overall reduction in the prevalence of dental caries in both deciduous and permanent teeth. The study highlights the need for reappraisal of the out-reach programmes to counter the large volume of untreated dental caries. The out-reach concept could be improved by incorporating appropriate modifications to its configurations to ensure optimal performance keeping in line with its’ prime objectives.